FIGURE 9 in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 9. Cladaster analogus. "small form" USNM 1116312. A. Abactinal surface. B. Close-up of abactinal plates and granules. C. Actinal surface. D. Armtip showing penultimate superomarginal plates. Scale Bar = 0.5 cm. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 22, DOI: 10.5281/zenodo.276783